2010
DOI: 10.1007/s10750-010-0271-2
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of fish farming on plankton structure in a Brazilian tropical reservoir

Abstract: This study investigated the effects of fish farming on phytoplankton and zooplankton structure in a Brazilian tropical reservoir. Samplings were undertaken among 15 net cages and upstream and downstream of the cages over a 120-day period. Soon after the tilapia feeding, we observed the highest density of phytoplankton, with dominance of Cyanobacteria which probably increased due to the increase in predation pressure by cladocerans and copepods on the Cryptophyceae. However, after 30 days from that, a reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 43 publications
8
46
0
3
Order By: Relevance
“…Borges et al (2010), in experiment with tilapia (Oreochromis niloticus L.) in net cages in an arm of Rosana reservoir, observed an increase in the concentration of total nitrogen and ammonium after the installation of the net cages, and also found strong influence of the reservoir hydrodynamics on the cultivation system. Indeed, the hydrodynamic has been pointed out by several authors (Diaz et al, 2001;Silva et al 2005;Araripe et al, 2006;Alves and Baccarin, 2007;Nogueira et al 2010) as driving the changes to the abiotic variables.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Borges et al (2010), in experiment with tilapia (Oreochromis niloticus L.) in net cages in an arm of Rosana reservoir, observed an increase in the concentration of total nitrogen and ammonium after the installation of the net cages, and also found strong influence of the reservoir hydrodynamics on the cultivation system. Indeed, the hydrodynamic has been pointed out by several authors (Diaz et al, 2001;Silva et al 2005;Araripe et al, 2006;Alves and Baccarin, 2007;Nogueira et al 2010) as driving the changes to the abiotic variables.…”
Section: Discussionmentioning
confidence: 97%
“…Chlorophyceae and Cyanobacteria are widely distributed and have usually been associated to greater availability of nutrients and light and high temperature conditions (Huszar et al, 2000;Komárek, 2003;Sant'Anna et al, 2006b;Lachi and Sipaúba-Tavares, 2008). In addition, some studies have observed an increase in phytoplankton density and biomass due to the selective consumption of the zooplankton and consequent dominance of Cyanobacteria (Degans and Meester, 2002;Kozak and Goldin, 2004;Borges et al, 2010). Cyanobacteria and Chlorophyceae were particularly represented by Chroococcales and Chlorococcales, respectively, especially colonial nanoplanktonics, that presented high surface/volume ratio, which increases the absorption of nutrients allowing adaptive advantages (Lopes et al, 2005;Dantas et al, 2008;Brasil and Huszar, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations